Exploring the Impact of Yoga Intervention on Psychological Symptoms in Irritable Bowel Syndrome Patients: A Randomized Controlled Study - Diksha Devi; Sandeep Bhattacharya; Sunita Tiwari; Adarsh Tripathi; Kalpana Singh; Sumit Rungta (International Journal of Yoga)
Background: Irritable bowel syndrome (IBS) is an extremely prevalent gastrointestinal disorder that has an unfavorable impact on the living standard and IBS-related multiple symptoms. 11%–15% of people worldwide are suffering from IBS. Secondary symptoms such as depression or anxiety are experienced by IBS patients. Yoga practices combined with traditional medical treatment can be a successful therapy for IBS. Objectives: The objective of this randomized control research was to observe the effectiveness of the yoga intervention as an add-on therapy in IBS patients with conventional treatment and its comparison with IBS with conventional treatment as a control. Materials and Methods: The suggested research is an open-blinded, prospective, randomly assigned, single-center, parallel-group, and end-point trial. Patients with IBS who satisfied the Rome Ⅳ criteria for diagnosis were recruited and randomly allocated into two groups: Intervention Group A (Yoga + conventional treatment) and Control Group B (Conventional treatment only). Group A (n = 85) received yoga intervention five times a week for 3 months, and Group B (n = 80) took their prescribed medication without yoga intervention. Psychological symptoms and IBS severity scores before and after yoga intervention were measured and compared with the control group with the help of validated questionnaires: Depression, Anxiety, and Stress Score (DASS-21) and IBS Severity Score, respectively. Results: The body weight and body mass index after 3 months of follow-up were significantly lowered (P < 0.05) in the yoga intervention group as compared to the control group. The overall severity of IBS after yoga interventions in Group A (259.2 ± 49.9–256.1 ± 48.6, P < 0.01) was significantly reduced than the control group (270 ± 56.6–271.9 ± 54.8, P > 0.05). Moreover, the psychological stress (P < 0.05) and anxiety (P < 0.01) scores were also significantly decreased after 3 months of follow-up in the yoga intervention group. The serum cortisol level was decreased in Group A. However, it could not reach a significant level. Conclusion: The current study indicates an affirmative result of yoga intervention along with conventional treatment for patients with IBS might be strongly advised.